(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper interrogates Kenyan politics through the lenses of Niccolo Machiavelli’s ideas on political power. It analyses the relevance of Machiavelli’s political ideas, as they have applied by different political leaders in Kenya. It pays special attention at how over the years Kenyan politicians at the helm of Kenyan political stage, the state house, have shrewdly mastered and used religion channelise politics of their times. Colonial rule in Kenya witnessed the emergence of a profoundly unbalanced institutional landscape and underdevelopment. With all capacity resided in a strong prefectural provincial administration, political parties remained underdeveloped making Kenyan politics to be leader centred. Politics is perceived as a game in which interests clash and political leaders attempt to establish stability amid conflicting interests. This reality is captured in the ideas of Machiavelli, whose works in political philosophy created the ideological ground for the emergence of Machiavellianism. The most significant aspect of colonialism in Kenya was political domination control, underdevelopment and authoritarianism. Colonialism in Kenya between 1895-1963 was characterized by economic exploitation and colonial expression. Sadly, the spectre of repression, exploitation and underdevelopment persisted in independent Kenya all against the hopes Kenyans had at independence. In this work, we argue that the post independence history of Kenya is replete with key aspects of Machiavelli’s conception of political power, ‘ misuse’ of religion by leaders and glaring underdevelopment all in the name of managing politics. Therefore, this paper examines the application of Machiavellian principles in the independent Kenya between 1963 and 2007.